Biologics in gastrointestinal and pancreatic neuroendocrine tumors - Liu, Iris H.; Kunz, Pamela L. (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
The development of biologic agents has ushered in a new era of precision medicine, opening the door to new therapeutic options designed to intelligently target cancer cells and their promoting factors, while leaving normal cells relatively unharmed. Biologics for the treatment of neuroendocrine tumors (NETs) have followed in the footsteps of regimens targeting pathways upregulated in other cancers, including the vascular endothelial growth factor (VEGF) and the mammalian target of rapamycin (mTOR). Through a number of clinical trials, the mTOR inhibitor everolimus and the receptor tyrosine kinase (RTK) inhibitor sunitinib were recently approved for NETs. Other biologics such as the VEGF-A inhibitor bevacizumab have also demonstrated promising clinical activity in NETs. Interestingly, though trials have demonstrated the efficacy of everolimus and sunitinib in extending progression-free survival (PFS) in NETs, objective response rates (RR) are uniformly low, indicating that the primary effect of these drugs is maintenance of stable disease. Due to the relatively indolent nature of the more common, well-differentiated variety of NETs, stable disease is often a reasonable goal for NET patients. Well-differentiated NETs have been shown to be poor responders to cytotoxic chemotherapy, underlining the important role of biologics in treating and managing NETs and their hormonal symptoms. Ongoing and future trials are investigating a wide variety of biologic compounds in NETs, including other RTK inhibitors, mTOR pathway inhibitors, and immune checkpoint inhibitors. Within this review, we will discuss major trials leading up to the FDA approval of everolimus and sunitinib for NETs, as well as other promising biologics currently under investigation in NET clinical trials.